The OmegaWhite survey for short-period variable stars – VII. High amplitude short-period blue variables. Issue 2 (12th April 2022) - Ramsay, Gavin; Woudt, Patrick A; Kupfer, Thomas; van Roestel, Jan; Paterson, Kerry; Warner, Brian; Buckley, David A H; Groot, Paul J; Heber, Ulrich; Irrgang, Andreas; Jeffery, C Simon; Motsoaledi, Mokhine; et al.
ABSTRACT: Blue Large-Amplitude Pulsators (BLAPs) are a relatively new class of blue variable stars showing periodic variations in their light curves with periods shorter than a few tens of minutes and amplitudes of more than 10 per cent. We report nine blue variable stars identified in the OmegaWhite survey conducted using ESO's VST, which shows a periodic modulation in the range 7–37 min and an amplitude in the range 0.11–0.28 mag. We have obtained a series of followup photometric and spectroscopic observations made primarily using SALT and telescopes at SAAO. We find four stars which we identify as BLAPs, one of which was previously known. One star, OW  J0820–3301, appears to be a member of the V361 Hya class of pulsating stars and is spatially close to an extended nebula. One further star, OW J1819–2729, has characteristics similar to the sdAV pulsators. In contrast, OW J0815–3421 is a binary star containing an sdB and a white dwarf with an orbital period of 73.7 min, making it only one of six white dwarf-sdB binaries with an orbital period shorter than 80 min. Finally, high cadence photometry of four of the candidate BLAPs show features that we compare with notch-like features seen in the much longer period Cepheid pulsators.